A comparative laboratory trial evaluating the immediate efficacy of fluralaner, afoxolaner, sarolaner and imidacloprid + permethrin against adult Rhipicephalus sanguineus (sensu lato) ticks attached to dogs. Issue 1 (December 2016) - Burgio, Federica; Meyer, Leon; Armstrong, Rob
Abstract Background Acaricides are used to treat and prevent tick infestations, and a common clinical scenario is to administer an acaricide on observing an attached tick. Consequently, immediate acaricidal efficacy (onset of activity and speed of kill) results are clinically valuable. This study evaluated the immediate efficacy of four commercially available acaricides against adultRhipicephalus sanguineus (sensu lato ). Methods Forty dogs were blocked on hair length and tick carrying capacity, then randomly assigned to receive one of four treatments (fluralaner, sarolaner, imidacloprid + permethrin, or afoxolaner) or left untreated as controls. All dogs were challenged with 50 adultR. sanguineus (s.l .) ticks 48 h prior to treatment. After treatment, in situ tick thumb counts were conducted at 2, 4, 8, 12 and 24 h; thereafter ticks were removed and counted at 48 h. Results Imidacloprid + permethrin had the earliest onset of activity at 2 h (36.9% efficacy) followed at 4 h by fluralaner (60.2% efficacy) and sarolaner (48.2% efficacy), and lastly afoxolaner at 8 h (90.8% efficacy). Three oral treatments had an 8 h speed of kill (>90% efficacy) threshold; with corresponding efficacies as: fluralaner (99.6%), sarolaner (94.7%) and afoxolaner (90.8%). Fluralaner and sarolaner achieved 100% efficacy at 12, 24 and 48 h; afoxolaner achieved 100% efficacy at 48 h. Imidacloprid + permethrin achieved 80.1% efficacy at 48 h, therefore, failing to attain the speed of kill 90% efficacy threshold. Conclusion The systemically distributed isoxazolines performed much better than cutaneously distributed imidacloprid + permethrin and are optimal treatment choices against attached ticks based on the combination of earlier onset of activity and speed of kill. Fluralaner had a 4 h onset of activity, an 8 h speed of kill and achieved 100% efficacy at 12 h.